Manejo odontológico de anestésicos locales en pacientes hipertensos - Lizeth Carolina, Cruz Chavarrea (2021)
ABSTRACT Arterial hypertension is a systemic disease with a very high prevalence worldwide, considered a public health problem and of interest to the public and private health sectors, local anesthetics for their part are drugs widely used in dentistry to prevent the conduction of electrical impulses, its use in hypertensive patients in dental care is widespread. This research aimed to analyze the dental management of local anesthetics in hypertensive patients, by compiling bibliographic information from articles published between 2010-2020, using databases of academic relevance with a total of 70 publications that complied strict information quality. The research determined that the use of local anesthetic with adrenergic vasoconstrictor is safe to use in controlled hypertensive patients or stage I and II limiting it to a maximum recommended dose of 0.04 mg to 0.054 mg as 2% lidocaine with epinephrine 1,100,000 two to three cartridges, while in uncontrolled patients or stage 3 or 4 hypertension, the use of anesthetic with adrenergic vasoconstrictor is not indicated. It is suggested that the dentist should always take blood pressure at each dental consultation, maintain communication with the treating physician and perform a good anesthetic technique to safeguard this type of patient and successfully perform the clinical procedure. Keyword: Arterial Hypertension, local anesthetics, vasoconstrictors. Reviewed by: Dra. Nelly Moreano Ojeda ENGLISH PROFESSOR c.c. 1801807288